A Quick Evaluation Study of Training and Visits System - Planning Commission (Planning Commission, 1982)
Five Year Plans in India have accorded a very high priority to Agriculture Extension Programmes for the development of agriculture sector. The first stop in this direction was the introduction of Community Development Programme and National Extension Services in 1952. Subsequently, various programmes such as Intensive Agriculture development Programme (IADP), Intensive Agriculture Area Programme (IAAP), High Yielding Varieties (HYV), Small Farmers Development Agency (SFDA) and Marginal Farmers and Agricultural Labourers (MFAL), etc. were taken an up in different Plans for the benefit of agriculturists.
Programme Evaluation Organisation Planning Commission Government of India New Delhi